THE ROLE OF CHESS IN DEVELOPING CRITICAL THINKING SKILLS AMONG PRIMARY SCHOOL STUDENTS (Sport Science Research, 2025)
This article comprehensively examines the role of chess in developing critical thinking skills among primary school students. The study aims to provide a scientific analysis of the impact of chess on the formation of cognitive and logical skills, as well as on enhancing students’ cognitive activity. The authors assess the pedagogical effectiveness of integrating chess into the educational process using experimental and empirical methods.The study consisted of three main stages: a diagnostic (ascertaining) experiment, the implementation of chess elements into the learning process, and a formative experiment. At each stage, changes in students’ logical, critical, and creative thinking were evaluated. The findings indicate that playing chess significantly improves students’ decision-making, information analysis, and problem-solving abilities.In addition, the study employed questionnaires, observation, and cognitive testing methods. The results demonstrated a positive impact of chess on students’ learning motivation and attention stability. According to the experimental data, the proportion of students with a high level of critical thinking increased from 22% to 64%, while the proportion of students with a low level decreased from 30% to 6%. The statistical significance of these results was confirmed using a t-test (p < 0.05).The article also includes a review of domestic and international scientific literature and provides a theoretical analysis of the advantages of chess in education. The findings confirm that integrating chess into primary education curricula positively affects the quality of education and students’ cognitive development. Furthermore, the study contributes to the modernization of Kazakhstan’s education system by proposing methodological foundations for using chess as a pedagogical tool.
Keywords: chess; critical thinking; primary education; cognitive activity; teaching methodology; creativity